Potential Correlation between the Decadal East Asian Summer Monsoon Variability and the Pacific Decadal Oscillation - Lei, Yu (Atmospheric and oceanic science letters = Daqi-he-haiyang-kexue-kuaibao, 2013)
This study discusses the potential contribution of the Pacific decadal oscillation （PDO） to the weakening of the East Asian summer monsoon （EASM） and the evident correlation between the positive PDO and ＂Southern flood and Northern drought （SFND）＂ summer rainfall pattern over East China.The mechanism behind this contribution is also discussed.